Integrated Metabolomics and Lipidomics Analysis Reveal Remodeling of Lipid Metabolism and Amino Acid Metabolism in Glucagon Receptor–Deficient Zebrafish - Bai, Xuanxuan; Jia, Jianxin; Kang, Qi; Fu, Yadong; Zhou, You; Zhong, Yingbin; Zhang, Chao; Li, Mingyu (Frontiers in Cell and Developmental Biology, 2021)
The glucagon receptor (GCGR) is activated by glucagon and is essential for glucose, amino acid and lipid metabolism of animals. GCGR blockade has been demonstrated to induce hypoglycemia, hyperaminoacidemia, hyperglucagonemia, decreased adiposity, hepatosteatosis and pancreatic α cells hyperplasia in organisms. However, the mechanism of how GCGR regulates these physiological functions is not yet very clear. In our previous study, we revealed that GCGR regulated metabolic network at transcriptional level by RNA-seq using GCGR mutant zebrafish (gcgr-/-). Here, we further performed whole-organism metabolomics and lipidomics profiling on wild type and gcgr-/- zebrafish to study the changes of metabolites. We found 107 significantly different metabolites from metabolomics analysis and 87 significantly different lipids from lipidomics analysis. Chemical substance classification and pathway analysis integrated with transcriptomics data both revealed that amino acid metabolism and lipid metabolism were remodeled in gcgr-deficient zebrafish. Similar to other studies, our study showed that gcgr-/- zebrafish exhibited decreased ureagenesis and impaired cholesterol metabolism. More interestingly, we found that the glycerophospholipid metabolism was disrupted, the arachidonic acid metabolism was up-regulated, and the tryptophan metabolism pathway was down-regulated in gcgr-/- zebrafish. Based on the omics data, we further validated our findings by revealing that gcgr-/- zebrafish exhibited dampened melatonin diel rhythmicity and increased locomotor activity. These global omics data provide us a better understanding about the role of GCGR in regulating metabolic network and new insight into GCGR physiological functions.